STRATEGI PENGEMBANGAN PROFESIONALITAS GURU MELALUI PENDIDIKAN DAN PELATIHAN - Wiwu Ulandari; Rustan Santaria (Institut Agama Islam Negeri (IAIN) Palopo, 2020)
One of the keys of education success is the teacher. The teacher plays an important role in the learning process to improve the quality of students. Therefore the professionalism of a teacher is very important to note. Professional teachers are those who are able to carry out their duties as educators to the maximum by having the ability and expertise as an educator. This research is library research. The theory is obtained from the library data then investigated it to find out the conception objective result. The result of this research is to realize the goals of education, appropriate development strategies are needed in order to improve teacher professionalism. There are some step that have to done in holding education and training they are need analysis, goal setting, building program content and program evaluation. Education and training is a development strategy that aims to improve teacher competence in terms of knowledge, skills and attitudes.